Kvantitativne razlike funkcionalnih sposobnosti vaterpolista klasificiranih prema razlicitim pozicijama u igri - Popo, A.; Dedovic, D.; Colakhodzic, E.; Novakovic, R. (Sportski Logos, 2015)
This research has the character of transversal study with the aim of determining the differences in the dimensionality of the functional abilities, with junior water polo Adriatic League, sorted by position in the game, and thus create a model that will be representative for the selection and training process in water polo. Functional differences according to positions on the team with junior water poloAdriatic League have aimed to show the real state of diversity of individual positions of water polo players from this anthropological area. The study included 5 variables of functional area, which clearly displayed the state of water polo players according to their positions on the team. Positions on the team are devided into forwards(wingers and external players), the centers, the guards and at the end goalkeepers. In order to monitor players, whose characteristics of the functional area in this sport is very important and which give the real state of fitness, tests are set with explicitly clear measurements in swimming pools and gyms for the seven clubs competing in the Adriatic water polo league. It is very important to analyze the functional area of water polo players, not only in order to evaluate variations in size in quantitative and qualitative terms, but also for the selection of players in certain competitive categories and for certain positions in the team.The total sample of respondents (n =104) is made of seven clubs which participate in the same level of competition in the Adriatic waterpolo League. In this case, the results suggest to equal values of functional abilities of water polo players measured by their positions. It is presumable why the researche didn't lead to any statistically significant differences. One of the reasons is that the set of tests for evaluation of functional abilities or characteristics can not successfully differentiate water polo players playing on different positions. Therefore, the author's recommendation for the similar future researches is to select extensive set of variables in order to obtain objective information.